Brand Expertise and Unhealthy Lifestyle Behaviors Drive Instant Noodle Purchase Decisions Among University Students, with Materialism as a Moderating Variable - Yudhia, Yudhia; Gunarto, Muji (International Journal of Marketing & Human Resource Research, 2025)
Instant noodles are classified as fast food and are widely favored among university students due to their ease of preparation, affordability, availability, and long shelf life. This study aims to examine the influence of brand expertise and unhealthy lifestyle behaviors on the purchase of instant noodles among university students, with materialism serving as a moderating variable. The research used a survey method with a probability sampling technique, specifically simple random sampling. The data were analyzed using regression analysis methods with a statistical approach, employing descriptive and inferential analyses such as regression tests and moderation tests to examine the research hypotheses. The analytical techniques include multiple linear regression analysis and Structural Equation Modeling (SEM). The findings indicate that brand expertise, unhealthy lifestyle behaviors, and materialism significantly influence the decision to purchase instant noodles among university students.